RHEOLOGICAL STUDIES ON VIRGIN, PLASTICIZED AND SOLID FILLED HTPB BINDER SYSTEM (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
The rheological studies on pure HTPB polymeric fuel binder system have been carried out as a function of shear rate (rpm) at different time intervals using Brookfield viscometer. The results obtained clearly indicate that the system behaves almost as a Newtonian fluid. However, with the lapse of time, the viscosity is seen to increase significantly at all shear rates. This is attributed to progressive increase in degree of cross-linking. Exactly a similar behavior is exhibited by plasticized binder at all shear rates with the difference that viscosity build up is at slower rates in comparison to pure binder due to dilution factor (reduced concentration) of reactants leading to reduced rate of cross-linking. The propellants (solid filled binder) also reflects similar behavior but with considerable increase in viscosity due to availability of lesser fluid responsible for flow